An analysis of the opening and closing verses in the holy Quran - Ali Kazemi; Mohammad Ali Salmani Nodoushan (Proceedings of AICS - Social Sciences, 2017)
The present qualitative study was concerned with the opening and closing verses in the Holy Quran. In effect, the study analyzed the opening and closing verses of 14 surahs to find out the central themes upon which they begin and come to a close. The analysis was conducted using the Persian translations of the verses as well as seeking help from the available Quran commentary or exegesis written in English. The analysis of the opening verses of the selected surahs revealed three central themes: (1) some surahs begin with words that praise and eulogize Allah, (2) some with imperative sentences or commandments addressed to the Holy Prophet, and (3) some related to specific events and times. Regarding the closing verses, the findings were not uniform across the selected surahs; while in some surahs the closing verses together with the opening verses deal with a similar topic or theme, in some other surahs the closing verses are concerned with different topics.